Lipopeptide antibiotic production by Bacillus velezensis KLP2016 - Khem Raj Meena, Tanuja Tandon, Abhishek Sharma, Shamsher S. Kanwar (Journal of Applied Pharmaceutical Science, 2018)
A bacterial strain isolated from a soil sample collected from Tamil Nadu Agriculture University, Coimbatore (India) was characterized as Bacillus velezensis KLP2016 by 16S rRNA molecular typing (Accession number KY214239). The extracellular lipopeptide was extracted from the cell-free fermentation medium of B. velezensis by acid-precipitation method. Optimized culture conditions enhanced the lipopeptide yield (2506 mg/L) from an earlier value of 1852 mg/L in the fermentation broth of B. velezensis KLP2016. The crude lipopeptide of B. velezensis showed 45.0 ± 1.2% and 70.6 ± 2.4% growth inhibition of Aspergillus niger and Mucor sp., respectively by the Agar well-diffusion assay on Potato Dextrose Agar (PDA) plates. The lipopeptide nature of the acid-precipitated fraction of B. velezensis was confirmed by the TLC and FTIR studies. The lipopeptide of B. velezensis exhibited strong (~90%) cytotoxic activity against Hep2-C human cervical carcinoma cells by MTT assay. The B. velezensis strain KLP2016 appeared to be a novel bacterium capable of producing potent antifungal and anticancer extracellular lipopeptide(s) in the fermentation broth.
Keywords: Anticancer activity, Antifungal activity, Bacillus velezensis, Lipopeptide.